Analytical study on maternal and fetal outcome of pre-eclampsia with severe features at tertiary care hospital - Chandrashekhara, Sushmitha S.; Devaraj, Revathi; Maliyuru Basavaraju, Asha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Pre-eclampsia is a multi-system, pregnancy specific disorder that is characterized by the development of hypertension and proteinuria after 20 weeks. Pre-eclampsia is the majority of referrals to tertiary care centre. It is one of the major causes of maternal and perinatal morbidity and mortality. Methods: A retrospective analytical study done over a period of six months from January 1st 2023 to June 30th 2023. Pregnant women admitted with PE with severe features to Cheluvamba hospital, MMCRI, Mysore during the study were considered and analysed using the proforma. Data was entered into Microsoft excel data sheet and was analyzed. Categorical data was represented in the form of Frequencies and proportions Results: Incidence of PE with severe features in our hospital was 3.4%. Majority (69%) were between 23-27 years of age and 52.7% were primigravida. Maternal complications were noted in 37.5% attributed to renal dysfunction, postpartum haemorrhage, DIC, placental abruption, HELLP, pulmonary oedema and postpartum eclampsia. Conclusions: Maternal and perinatal complications are more in patients with severe pre-eclampsia. The incidence of severe pre-eclampsia can be reduced by early referral, better antenatal care, early recognition and treatment of pre-eclampsia